Integration of 3D nanographene into mesoporous germanium. Issue 47 (23rd October 2020) - Sauze, Stéphanie; Aziziyan, Mohammad Reza; Brault, Pascal; Kolhatkar, Gitanjali; Ruediger, Andreas; Korinek, Andreas; Machon, Denis; Arès, Richard; Boucherif, Abderraouf
Abstract : Integration of nanographene in a 3D mesoporous structure of germanium. This opens a wide variety of applications requiring a high specific surface area. Abstract : Graphene is a key material of interest for the modification of physicochemical surface properties. However, its flat surface is a limitation for applications requiring a high specific surface area. This restriction may be overcome by integrating 2D materials in a 3D structure. Here, a strategy for the controlled synthesis of Graphene-Mesoporous Germanium (Gr-MP-Ge) nanomaterials is presented. Bipolar electrochemical etching and chemical vapor infiltration were employed, respectively, for the nanostructuration of Ge substrate and subsequent 3D nanographene coating. While Raman spectroscopy reveals a tunable domain size of nanographene with the treatment temperature, transmission electron microscopy data confirm that the crystallinity of Gr-MP-Ge is preserved. X-ray photoelectron spectroscopy indicates the non-covalent bonding of carbon to Ge for Gr-MP-Ge. State-of-the-art molecular dynamics modeling provides a deeper understanding of the synthesis process through the presence of radicals. The successful synthesis of these nanomaterials offers the integration of nanographene into a 3D structure with a high aspect ratio and light weight, thereby opening avenues to a variety of applications for this versatile nanomaterial.